IBU SANGGAR MARIA NYAK DESA G1. MATARAM - Wawan Syafutra; Mellin Andriana ($$8@@&&$%K, 2021)
The purpose of this study was to determine whether there was an effect of reducing fat levels on the women of Maria Nyak Village, G1 Village. Mataram after being given aerobic exercise treatment. This research is an experimental research that uses the One Group Pretest – Posttest Design. The population in this study were all members of the Maria Nyak Studio, G1 Mataram Village. The sample selected using the Random Sampling technique, amounting to 10 people. The data analysis used is the t-test statistic. The instrument used in this study was to use a caliper to measure fat content. The results of the initial test mean 43.7 and the final test with a mean of 33.6. From these results it has a difference of 10.1 with a t count value of 6.899 and a t table value of 1.883 with a significance of 0.00 > 0.05. So it can be concluded that the aerobic exercise method can reduce fat levels.